Risiko Usahatani Padi Lahan Sawah di Desa Mranggen Kecamatan Pulokarto Sukoharjo - Efi Nikmatu Sholihah; Dewi Ratna Nurhayati; Novinda Elly Alyanissa (Program Studi Agribisnis Fakultas Pertanian, 2026)
This study aims to analyze the level of production risk and identify factors influencing this risk in lowland rice farming in Mranggen Village, Polokarto District, Sukoharjo Regency. The approach used in this study was a descriptive, quantitative method, involving 30 rice farmers as respondents. Data were collected through interviews, questionnaires, and field observations. Risk analysis was conducted by calculating the coefficient of variation, while factors influencing production risk were analyzed using multiple regression with the Ordinary Least Squares (OLS) approach. The results showed that the coefficient of variation value of rice production was 0.03, indicating that production risk was relatively low. Seed factors significantly influenced the reduction of production risk (risk-reducing factor), while other variables, such as organic fertilizer, inorganic fertilizer, pesticides, and labor, did not have a significant effect. This study emphasizes the importance of using superior seeds that are adapted to climate change and resistant to pests and diseases in reducing production risk.